2014
DOI: 10.1021/jp4100729
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Crystal Formation at the “Nafion–Water” Interface

Abstract: In our recent work [Bunkin et al. Water 2013, 4, 129-154] it was first obtained that the water layer, having a size of several tens of micrometers and being adjacent to the swollen Nafion interface, is characterized by enhanced optical density; the refractive index of water at the interface is 1.46. Furthermore, the birefringence effect was observed in this layer. To explain these results, it has been hypothesized that because of "disentangling" of charged polymer chains from the Nafion surface toward the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
4
22
0
1
Order By: Relevance
“…It is clear that this effect cannot be attributed to the chemical reaction represented by Equation (12); as we know, there is no physical mechanism for the frequency filtering due to chemical reactions. However, as shown in [13] (see also our recent work [16]), the water in the EZ has a quasicrystalline structure. Therefore, the dynamics of the processes responsible for the chemiluminescence (the radiative ROS recombination, see Formulas (9)- (11)), has its own specificity in the EZ as compared with the bulk water.…”
Section: Analysis Of the Coherence Of The Self-oscillating Modesmentioning
confidence: 52%
See 1 more Smart Citation
“…It is clear that this effect cannot be attributed to the chemical reaction represented by Equation (12); as we know, there is no physical mechanism for the frequency filtering due to chemical reactions. However, as shown in [13] (see also our recent work [16]), the water in the EZ has a quasicrystalline structure. Therefore, the dynamics of the processes responsible for the chemiluminescence (the radiative ROS recombination, see Formulas (9)- (11)), has its own specificity in the EZ as compared with the bulk water.…”
Section: Analysis Of the Coherence Of The Self-oscillating Modesmentioning
confidence: 52%
“…In our recent works [14,15] we show that the water layer adjacent to the Nafion interface has an increased (with respect to ordinary water) refractive index; furthermore, it was found that the EZ water exhibits birefringence properties, which implies the quasi-crystalline structure of that liquid (note that the birefringence of water inside the EZ was first observed in [9]). In our recent luminescent spectroscopy experiments [16] we demonstrated that these intriguing effects can be attributed to the formation of colloidal crystals in the EZ; such crystals are composed of negatively charged rod-like particles-the Nafion polymeric chains-which are disentangled in the bulk of water and are packed with a certain order. It is straightforward to assume that a large class of physical effects, which have been reliably observed in the bulk of liquid water, will exhibit some specificity in the EZ.…”
Section: Introductionmentioning
confidence: 97%
“…Hence, it is possible to detect 4-water by interference methods. [4][5][6][7] Unfortunately, judging from the available literature, this fact has not been addressed at the level it deserves.…”
Section: Discussionmentioning
confidence: 99%
“…3 The second example is an RI of a water n ≈ 1.43 at the hydrophilic surface of Nafion, a synthetic polymer with ionic properties. 4,5,6 Cells of most organisms contain as much as 80% of water; in jellyfish, the percentage exceeds 95%. Therefore, it is logical to assume that the component referred to as 4-water 2 somehow affects microscopic phase images of cells and is detectable in these objects.…”
Section: Introductionmentioning
confidence: 99%
“…We also became aware of the exclusion zone (EZ) found in interfacial water close to polyelectrolytes and its implication for the physiology of biological membranes and of blood flow in venules and capillaries (Zheng and Pollack [78]; Zheng et al [77]; Gouveia and Galembeck [26]; Chai and Pollack [6]; Bunkin et al [3]; Rohani and Pollack [53]). And finally, in 2014 in a Gerald Pollack seminar at Galembeck's institute, we became aware of the polar liquid bridges studied by Elmar C. Fuchs' group (see Fuchs et al [19] and Wexler et al [74] or better watch their videos 2 ).…”
Section: The Basement Membrane and Extracellular Matrix Are Both Excimentioning
confidence: 99%